Hydroponic cultivation of Oncidium baueri - Daniele Brandstetter Rodrigues; Adriane Marinho de Assis; Ricardo Tadeu Faria; Marcia Wullf Schuch; Roberta Marins Nogueira Peil (Semina: Ciências Agrárias, 2017)
In Brazil, orchid cultivation has been increasing steadily over the last few years and contributing significantly to the economy. It has been reported that several vegetable crops and ornamentals have been successfully grown by soilless cultivation. The orchid Oncidium baueri Lindl. is grown on pot substrates. Nevertheless, hydroponics is an excellent alternative, especially for the production of cut flowers and bare root plants. The objective of this study was to evaluate the development of Oncidium baueri on two soilless systems: (a) pots containing Amafibra® coconut fiber, carbonized rice husk, and pine bark (1:1:1) irrigated with nutrient solution every 15 d; and (b) a nutrient film technique (NFT) hydroponic system irrigated with nutrient solution daily. Shoot height, pseudobulb diameter, and number of sprouts were evaluated monthly. The number of flowering plants, number of flowers, dry mass of shoots, and dry mass of roots were evaluated 11 months after onset of experiment. The pot cultivation system yielded more flowers and higher values for all vegetative parameters than the NFT hydroponic system.